Food Sovereignty and Rights-Based Approaches Strengthen Food Security and Nutrition Across the Globe: A Systematic Review - Sampson, Devon; Cely-Santos, Marcela; Gemmill-Herren, Barbara; Babin, Nicholas; Bernhart, Annelie; Bezner Kerr, Rachel; Blesh, Jennifer; Bowness, Evan; Feldman, Mackenzie; Gonçalves, André Luis; James, Dana; Kerssen, Tanya; et al. (Frontiers in Sustainable Food Systems, 2021)
This systematic review assembles evidence for rights-based approaches–the right to food and food sovereignty–for achieving food security and adequate nutrition (FSN). We evaluated peer-reviewed and gray literature produced between 1992 and 2018 that documents empirical relationships between the right to food or food sovereignty and FSN. We classified studies by literature type, study region, policy approach (food sovereignty or right to food) and impact (positive, negative, neutral, and reverse-positive) on FSN. To operationalize the concepts of food sovereignty and the right to food and connect them to the tangible interventions and practices observed in each reviewed study, we also classified studies according to 11 action types theorized to have an impact on FSN; these included “Addressing inequities in land access and confronting the process of land concentration” and “Promoting gender equity,” among others. We found strong evidence from across the globe indicating that food sovereignty and the right to food positively influence FSN outcomes. A small number of documented cases suggest that narrow rights-based policies or interventions are insufficient to overcome larger structural barriers to realizing FSN, such as inequitable land policy or discrimination based on race, gender or class.